Capacity building for conservation: problems and potential solutions for sub-Saharan Africa. Issue 2 (1st June 2017) - O'Connell, M. J.; Nasirwa, O.; Carter, M.; Farmer, K. H.; Appleton, M.; Arinaitwe, J.; Bhanderi, P.; Chimwaza, G.; Copsey, J.; Dodoo, J.; Duthie, A.; Gachanja, M.; et al.
Abstract: To achieve their conservation goals individuals, communities and organizations need to acquire a diversity of skills, knowledge and information (i.e. capacity). Despite current efforts to build and maintain appropriate levels of conservation capacity, it has been recognized that there will need to be a significant scaling-up of these activities in sub-Saharan Africa. This is because of the rapid increase in the number and extent of environmental problems in the region. We present a range of socio-economic contexts relevant to four key areas of African conservation capacity building: protected area management, community engagement, effective leadership, and professional e-learning. Under these core themes, 39 specific recommendations are presented. These were derived from multi-stakeholder workshop discussions at an international conference held in Nairobi, Kenya, in 2015. At the meeting 185 delegates (practitioners, scientists, community groups and government agencies) represented 105 organizations from 24 African nations and eight non-African nations. The 39 recommendations constituted six broad types of suggested action: (1) the development of new methods, (2) the provision of capacity building resources (e.g. information or data), (3) the communication of ideas or examples of successful initiatives, (4) the implementation of new research or gap analyses, (5) the establishment of new structures within and between organizations, and (6) the development of new partnerships. A number of cross-cutting issues also emerged from the discussions: the need for a greater sense of urgency in developing capacity building activities; the need to develop novel capacity building methodologies; and the need to move away from one-size-fits-all approaches.